Territorial assemblages and Governance : The example of the Taonaba project (Town of Abymes, Guadeloupe) - Soulier, Eddie (2012)
This article reports on an action research to support the urban community of Cap Excellence in Guadaloupe in its local sustainable development project. After summarizing the terms of the debate around sustainable development, and presenting the region, the search will be put back into the context of a more general approach of territorial* intelligence (TI). The limits of a local Agenda 21 in the form of a 'programmed action plan' is the chance to enhance the concept of TI with that of territorial assemblage. Our study area is the natural reserve of the Grand Cul-de-Sac Marin of Guadeloupe, the second largest biosphere reserve designated by UNESCO in the archipelago of the Petites Antilles, more specifically the implementation of the Taonaba project, whose goal is to launch an ecotourism visitors' centre, operational at the end of 2012. Based on the analysis of a large amount of data, the article describes an evaluation tool for territorial assemblages for participative territorial governance. Our results were presented to local government officials in the Urban Sustainable Development Forum, which our group organised from 2 to 4 April 2012, in the district of Abymes/Pointe-à-Pitre